An investigation into the Bryozoa of Ireland including the distributional patterns of the marine Bryozoa of Ireland over the last 150 years - KELSO, ANTOINETTE (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2020)
Bryozoans are sessile filter feeding marine invertebrates. Research in Ireland on bryozoans has been sparse in recent years but many studies were carried out in the early 1900's by researchers such as Albert Russell Nichols (1859-1933). This study has a number of interlinked aims. It will evaluate the history of bryozoan research in Ireland and discuss the biologist Albert Russell Nichols (1859-1933) and his contribution to bryozoan research. Bryozoan diversity and distributional changes from Nichols' time have been examined very little, this study will examine any changes exhibited over the last 150 years. These changes will be evaluated using both a north south and east west divide by looking at historical records and the results of a recent sampling programme. A taxonomically ordered atlas using SEM images and photographs has been compiled of the bryozoans recorded from Ireland using both recent and historical records. In the last 15 years 4 non-native bryozoan species have been recorded in Ireland. Watersipora subtorquata, Tricellaria inopinata, Bugula neritina and Schizoporella japonica and other potential invasive bryozoans are discussed to evaluate their potential arrival methods and distribution around Ireland. Bugula neritina is often found as an epiphyte on algae and foliose bryozoans. The occurrence of bryozoan epiphytes and their substrate use is assessed here using specimens taken from 42 sites around Ireland.
APPROVED
Keywords: Bryozoa; Invasive bryozoa; Epiphytes; Albert Russell Nichols